2019
DOI: 10.1016/j.nedt.2019.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of nursing students perceptions of their training hospital's infection prevention climate: A multi-university study in Saudi Arabia

Abstract: A B S T R A C TBackground: The risk of acquiring and spreading infection must be minimized in nursing students because they are exposed to healthcare-associated infections during clinical training. To achieve this goal, students should be knowledgeable and competent in infection control practice before proceeding to their training hospitals. Objectives: This study assessed the nursing students' perception of the infection prevention climate in training hospitals in Saudi Arabia. It also examined the predictors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…However, the survey was conducted after the government closed all schools, and this situation may have interfered with the information dissemination efforts of some universities. Differences in infection prevention knowledge and practices among Saudi students were also observed in previous studies, which attributed these differences to varying course contents, teaching methodologies, and other curricular activities (23,24). Moreover, our findings indicated that female students had better knowledge than male students.…”
Section: Discussionsupporting
confidence: 81%
“…However, the survey was conducted after the government closed all schools, and this situation may have interfered with the information dissemination efforts of some universities. Differences in infection prevention knowledge and practices among Saudi students were also observed in previous studies, which attributed these differences to varying course contents, teaching methodologies, and other curricular activities (23,24). Moreover, our findings indicated that female students had better knowledge than male students.…”
Section: Discussionsupporting
confidence: 81%
“…The aforementioned multicenter study reported in [21] examined a single-point survey focusing on the impact of International Nosocomial Infection Control Consortium's (INICC) multidimensional approach on rates of central line-associated bloodstream infections and pneumonia in intensive care units in Saudi Arabia. A multi-university theoretical study in Saudi Arabia described nursing students' perception of the infection prevention climate of their training and provided unique perspective on factors that affect the infection prevention climate [25].…”
Section: Introductionmentioning
confidence: 99%
“…This finding is also true with actual knowledge, where students from University B scored higher than those from the other university. The differences in self-reported and actual diabetes knowledge between the students from the two universities may be related to several factors such as curricular content, teaching methodologies and strategies and the expertise of faculty members [ 19 ]. The nursing curriculum and course content in the two universities were not similar.…”
Section: Discussionmentioning
confidence: 99%